2019
DOI: 10.1002/adem.201901201
|View full text |Cite
|
Sign up to set email alerts
|

Static Electrification of Plastics under Friction: The Position of Engineering‐Grade Polyethylene Terephthalate in the Triboelectric Series

Abstract: There is an emerging trend to replace moving metallic parts, such as bearings or bushes, with plastic components. The electrostatic hazard associated with plastic components subject to mechanical friction is well documented, but the magnitude as well as physical–chemical origin of this phenomenon remains debated. Using atomic force microscopy and Faraday pail measurements, the triboelectrification of Ertalyte®, a commonly used bearing‐grade formulation of polyethylene terephthalate, when rubbed against other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This is approximately the same as silicon dioxide used in MOS structures 49 , 50 . The election affinity of poly(tetrafluoroethylene) fluoropolymer is cited as ~ − 0.8 eV 77 , compared to 0.9 eV for silicon dioxide 78 . Using these values, the value of the positive charge in the fluoropolymer layer is calculated to be 5.72 × 10 –7 C cm −2 (p-type MIS) and 5.11 × 10 –7 C cm −2 -n-type MIS).…”
Section: Resultsmentioning
confidence: 99%
“…This is approximately the same as silicon dioxide used in MOS structures 49 , 50 . The election affinity of poly(tetrafluoroethylene) fluoropolymer is cited as ~ − 0.8 eV 77 , compared to 0.9 eV for silicon dioxide 78 . Using these values, the value of the positive charge in the fluoropolymer layer is calculated to be 5.72 × 10 –7 C cm −2 (p-type MIS) and 5.11 × 10 –7 C cm −2 -n-type MIS).…”
Section: Resultsmentioning
confidence: 99%
“…However, this is not the case. Rubbing two pieces of the same material leads to static electricity. , This observation is mirrored by a related fact; that is, different formulations of a given polymer, such as polyethylene terephthalate in the form of either Mylar or Ertalyte, , take up different positions in the triboelectric series. This indicates that mechanochemical aspects underlie contact electrification, , including substrate softness, adhesion, and roughness …”
Section: Static Electricity: Charge and Electrostatic Potential Measu...mentioning
confidence: 99%
“…This phenomenon, referred to as contact- or triboelectrification, has widespread practical consequences and applications. For example, it underpins seemingly unrelated phenomena and technologies, such as a car’s static zip, the failure of automotive bearings, and the transfer of inks in xerography . The first written account on the static charging of an insulator is generally attributed to Thales of Miletus, who lived around 600 B.C .…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, over the last 5–10 years, a growing number of research groups have noticed one type of electrostatic field, which can be simply generated by contact electrification without any applied voltage or additives. Static charges develop on the surface of electrically insulating materials that are first brought in contact with and then macroscopically separated from another solid. , Recent studies show that this phenomenon is not limited to the solid/solid interface but also occurred at the liquid/solid or liquid/liquid interface. Based on the contact charging at the liquid/solid interface, our group developed a self-powered droplet triboelectric nanogenerator with spatially arranged electrodes as a probe for measuring the charge transfer (CT) between liquid and solid interfaces and showed that the electron transfer is the dominant CT species in the case of liquid/solid contact . This inevitably raises a challenge about the reproducibility of the chemical reaction in the liquid solution as chemical reactivity is governed by the movement and transfer of electrons, and electron transfer is most likely to occur at the interface between the reaction solution and the surrounding environment or the container, , such as air, beaker and pipette, when preparing the reaction solution.…”
Section: Introductionmentioning
confidence: 99%
“…7−10 Static charges develop on the surface of electrically insulating materials that are first brought in contact with and then macroscopically separated from another solid. 11,12 Recent studies show that this phenomenon is not limited to the solid/solid interface but also occurred at the liquid/solid or liquid/liquid interface. 13−19 Based on the contact charging at the liquid/solid interface, our group developed a self-powered droplet triboelectric nanogenerator with spatially arranged electrodes as a probe for measuring the charge transfer (CT) between liquid and solid interfaces and showed that the electron transfer is the dominant CT species in the case of liquid/solid contact.…”
Section: Introductionmentioning
confidence: 99%